Phytochemical composition and antioxidant activity of Euphorbia falcata/PEG biocomposites: a functional analysis using Saccharomyces cerevisiae - Pekdemir, Sibel Selcuk; Ozmen, Gorkem Kirmizikaya; Yilmaz, Okkes (Springer, 2025)
Biocompatible and biodegradable polyethylene glycol (PEG) composites were synthesized using ethanolic extracts of Euphorbia falcata at varying concentrations. These composites were introduced into Saccharomyces cerevisiae culture medium to evaluate their effects on phytochemical and biochemical responses. The structural characteristics of the composites were analyzed using Fourier-transform infrared spectroscopy (FT-IR), while thermal behavior was assessed via thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Upon exposure of yeast cultures to the composites, total protein levels, glutathione (GSH), glutathione disulfide (GSSG), and malondialdehyde (MDA) contents were quantified. Additionally, the levels of fat-soluble vitamins (A, D, E, K) and fatty acids were analyzed. Notably, the composite containing 25% E. falcata extract exhibited the highest total protein level (3.54 g/kg pellet), while pure E. falcata treatment resulted in the highest MDA concentration (341 nmol/g pellet), indicating oxidative stress. These findings highlight the potential of E. falcata/PEG biocomposites to modulate antioxidant responses and phytochemical activity in eukaryotic cells, suggesting possible applications in biomedical or food-related fields.
Keywords: PEG; Euphorbia falcata; Saccharomyces; Phytochemical; Physicohemical